Establishing fashion design entrepreneurs’ management competency in the Malaysian fashion landscape - Kamarulzaman, Zulina; Shaari, Nazlina (UiTM Press, 2024)
The achievements of Malaysian fashion designers have been fraught with success and failure. The intense competition in the fashion industry is one of the main obstacles for fashion designers who decide to venture into fashion entrepreneurship.This study seeks to understand what additional skills are necessary and how to face the challenges they encounter. The respondents in this study were fashion design entrepreneurs who participated in group discussions, and fashion experts who were interviewed. Throughout the entirety of the process of data collecting, a collection of standardised questionnaires was utilised in focus group discussions. As a consequence of the findings of the study, they are faced with the challenge of overcoming a variety of deficiencies, some of which include inadequate business management, inadequate financial management, inadequate management of human resources, and other deficiencies. Based on the findings, fashion experts who participated in this study have provided advice. As a result, this study can provide fashion design entrepreneurs with preventative business continuity and sustainability measures.